Serum 25-hydroxyvitamin D and bone turnover markers in Palestinian postmenopausal osteoporosis and normal women - Kharroubi, Akram; Saba, Elias; Smoom, Riham; Bader, Khaldoun; Darwish, Hisham (Archives of osteoporosis, 2017)
Summary This study evaluated the association of vitamin D and bone markers with the development osteoporosis in Palestinian postmenopausal women. Even though vitamin D deficiency was very high for the recruited subjects, it was not associated with osteoporosis except for bones of the hip. Age and obesity were the strongest determining factors of the disease. Purpose The purpose of this study was to investigate the association of bone mineral density (BMD) with serum vitamin D levels, parathyroid hormone (PTH), calcium, obesity, and bone turnover markers in Palestinian postmenopausal women. Methods Three hundred eighty-two postmenopausal women (≥45 years) were recruited from various women clinics for BMD assessment (131 women had osteoporosis and 251 were normal and served as controls). Blood samples were obtained for serum calcium, PTH, 25(OH)D, bone formation (N-terminal propeptide (PINP)), and bone resorption (serum C-terminal telopeptide of type I collagen (CTX1)) markers. Results Women with osteoporosis had statistically significant lower mean weight, height, body mass index (BMI), and serum calcium ( p < 0.05) compared to controls. No significant differences were detected between the mean values of bone turnover markers (CTX and PINP), 25(OH)D, and PTH of the two groups. Women with vitamin D deficiency (severe and insufficiency) represented 85.9% of the study subjects. Multiple and logistic regression showed that age and BMI significantly affected BMD and vitamin D had a significant association with BMD only at the lumbar spine. BMI was positively correlated with BMD and PTH but negatively correlated with vitamin D. Logistic regression showed that the odds ratio (OR) for having osteoporosis decreased with increasing BMI (overweight OR = 0.11, p = 0.053; obese OR = 0.05, p = 0.007). Conclusions There was no direct correlation between BMD and PTH, bone turnover markers, and vitamin D except at the lumbar spine. A negative correlation between BMD and age and a positive correlation with BMI were observed. The protective effect of obesity on osteoporosis was complicated by the effect of obesity on vitamin D and PTH.